Extended DPL-VIKOR Method for Risk Assessment of Technological Innovation Using Dual Probabilistic Linguistic Information - Shahzaib Ashraf; Muhammad Ijaz; Muhammad Naeem; Saleem Abdullah; Lula Babole Alphonse-Roger (Journal of Mathematics)
The main objective of the present study is to evaluate the multicriteria group decision-making problem in risk management for technological innovation projects (TIPs) under dual-probabilistic linguistic information. The suggested approach is based on an enhanced dual probabilistic linguistic-vise kriterijumska optimizacija kompromisno resenje (DPL-VIKOR) technique to assess risk management in TIP employing probabilistic linguistic information. The conventional VIKOR approach is incapable of dealing with the complexity and difficulty of risk assessment in TIP. Therefore, we incorporated the information included in the dual probabilistic linguistic term set. In DPL-VIKOR, we investigated the relationship between the positive ideal solution (PIS) of the alternative and the negative ideal solution (NIS). To deal with the multicriteria group decision-making problem of risk assessment in TIP, we proposed the extended DPL-VIKOR approach rather than the traditional VIKOR method. We compared the findings to those of several decision-making problem techniques and examined the effectiveness and reliability, as well as advantages of the proposed approach. From the comparison and sensitivity analysis, we conclude that the proposed method is more reliable and effective for evaluating the best alternative in risk management problems for TIP.